Aplicação do Na2S2O8, H2O2 e ferro na remediação de solos (latossolo e areia destrófica) contaminados com diesel - Fernandes, Hermano Gomes (2014)
Environmental liabilities from accidents in the retail petroleum industry, especially in urban areas, have represented a serious problem whose impact reaches the underground, people's health and even economic losses with the remediation process. In U.S.A. are estimated hundreds of billions of dollars invested in soil remediation processes. The results of the reports and investigative reports of liabilities in fuel stations distributed in the urban area of Natal-RN were used to estimate the local scenario of contamination. This database has been possible to determine the main contaminants (BTEX, PAHs, TOC), affected neighborhoods and types of potentially more impacted soils. Experiments were carried out in order to reverse contamination of this scenario, where the soil type was a factor in the planning, because it influences directly on the effectiveness of remediation techniques studied: Oxidation by hydrogen peroxide and oxidation by sodium persulphate. These oxidants are activated forming free radicals (HO•-, SO4 •-, HO2 • , O2 •-, S2O8 -2, etc) responsible for to mineralize the hydrocarbons and other organic compounds (releasing O2 e CO2). In the activation process, the ferrous ions (II) and ferric (III) were studied as well as hydrogen peroxide activation technique with sodium persulfate, the latter being presented the best efficiency among all the study, when activated with Fe+3. In addition to defining the most efficient technique, the aim of this study was to evaluate the influence of different soils among oxidative techniques, characterizing the effect of the concentration of these oxidants and also the concentration of the catalysts. Exists in most scenarios evaluated the presence of intrinsic total iron soil matrix. The so-called latosols present microaggregates reddish indicating the presence of these reactive species like iron and clayey aspect. The kinetic study was conducted by experimental design and monitoring of the percentage of total carbon (SSM-5000A) in the solid and liquid phases, knowing that 82.4% of the diesel molecule is carbon. Yet organic carbon and pH of liquid samples were analyzed for technical, characterizing the influence of soil type and its operating condition. The Fenton-like technique H2O2 e Fe+2 presented satisfactory oxidation, including sandy soil, but well below the best result. The sodium persulphate only activated with temperature, even in the most favorable soil, did not provide good efficiency. The best technique in the study had the concentration profile with 2,2x10- 1mol.L-1 of Na2S2O8 activated with 6,53x10-1mol.L-1 of H2O2 and 2,5x10-2 Fe3+mol.L-1 which reduced in less than a day 96 contamination in red soil, initially with 66,667 mg of diesel per kg of clean soil